On the Processing and Analysis of Microtexts: From Normalization to Semantics - Yerai Doval; David Vilares (Proceedings, 2018)
User-generated content published on microblogging social platforms constitutes an invaluable source of information for diverse purposes: health surveillance, business intelligence, political analysis, etc. We present an overview of our work on the field of microtext processing covering the entire pipeline: from input preprocessing to high-level text mining applications.